Squalus acanthias Linnaeus 1758 - De, Sarah T.; De, Marcelo R.; Gomes, Ulisses L. (Zenodo, 2016)
Squalus acanthias Linnaeus, 1758 (Figs. 2–15, Tables 1 –4) Spotted spiny dogfish; Piked dogfish; Cação-bagre-espinhoso (Portuguese) Squalus acanthias Linnaeus, 1758: 233 (original description, “Oceano Europaeo”); Rafinesque, 1810: 45 (listed; Sicily); Gill, 1862: 405 (cited; global); Poey, 1868: 213, 454 (cited; Cuba); Berg, 1895: 5, 6 (listed; Argentina, Uruguay); Jordan & Evermann, 1896: 54 (listed; North and Central America); Schreiner & Ribeiro, 1903: 79 (listed; Brazil); Regan, 1908: 45, 46 (identification key, listed; global); Garman, 1913: 192, plates 14 (figs. 1–4), 43 (figs. 9, 10), 59 (figs. 1, 2) (description; global); Fowler, 1936: 69 –71, figs. 19, 20 (revision; Eastern Atlantic); Bigelow & Schroeder, 1948: 455 –473, figs. 87 (A– D), 88 (revision; Northwestern Atlantic); Bigelow & Schroeder, 1953: 47–51, fig. 17 (description, cited; Western North Atlantic); Bigelow, Schroeder & Springer, 1953: 221 (cited; Western Atlantic); Bigelow & Schroeder, 1957: 30, fig. 3 D (description; global); Garrick, 1960: 520, figs. 1 (A–C), 3 (G–M), 5 (revision; New Zealand); Bass et al ., 1976: 13, 14, figs. 8 (F–G), 9 (revision; Eastern South Africa); Cadenat & Blache, 1981: 46 –48; fig. 28 (A–E) (revision; Mediterranean Sea); Lucena & Lucena, 1981: 2, fig. 3 (listed; Brazil); Compagno, 1984: 109 -113 (revision; global); Kondyurin & Myagkov, 1984: 118 –120, fig. 1 A (revision; Western Atlantic); Menni et al ., 1984: 62, 83, 84 (listed; Argentina, Uruguay); Myagkov & Kondyurin, 1986: 1 –20, fig. 1 (A, E, F, H) (revision; Atlantic); López et al ., 1996: 7, 8 (listed; Argentina); Cousseau & Perrotta, 1998: 34–35 (description; Argentina); Lessa et al ., 1999: 26, 61, 150 (cited, listed; Brazil); Mazzoleni & Schwingel, 1999: 114 (listed; Itajaí, Brazil); Gadig, 2001: 29, 36, 54–57, fig. 27 (description; Brazil); Soto, 2001: 94, 95 (listed; Brazil); Compagno, 2002: 380, 381, 383 (revision; South Atlantic); Nion et al ., 2002: 4 (listed; Uruguay); Haimovici et al ., 2003: 38, 39 (cited; Brazil); Meneses & Paesch, 2003: 7, 25, 45 (cited; Argentina); Smith & Heemstra, 2003: 61, 62, fig. 5.24 (identification key; description; South Africa); Heemstra & Heemstra, 2004 (cited, Southern Africa): 54; Soto & Mincarone, 2004: 73, 74 (listed; Brazil); Lamilla & Bustamante, 2005: 9, 26 (cited; Chile); Nelson, 2006: 66 (listed; global); Menni & Lucifora, 2007: 3 (cited; Argentina, Uruguay); Pon & Gandini, 2007 (cited; Argentina); Carrier et al ., 2010: 44, 127, 139 (cited); Gomes et al ., 2010: 44, 45 (cited; Brazil); Menni et al ., 2010 (cited; Southwestern Atlantic); Saéz et al ., 2010: 623 (identification key; Chile); Viana, 2011: 28 –56 (description; Southwestern Atlantic); Menezes, 2011: 4 (listed; Southern Brazil); Rosa & Gadig, 2014: 92 (listed; Brazil). Squalus fernandinus Molina, 1782: 188, 189, 285 (original description, not illustrated; Chile); Regan, 1908: 45, 46 (cited; Chile); Bigelow, Schroeder & Springer, 1953: 220–222 (cited; Western Atlantic). Acanthorhinus acanthias : Bigelow & Schroeder, 1948: 452 (in synonymy of S. acanthias ). Spinax acanthias : Cuvier, 1817: 130 (cited); Cuvier, 1863: 320 (listed); Bigelow & Schroeder, 1948: 452 (in synonymy of S. acanthias ). Acanthias vulgaris Risso, 1826: 13 (original description, not illustrated; Mediterranean, Sea); Müller & Henle, 1841: 83 (description); Duméril, 1865: 437 (description); Günther, 1866: 384, 396 (listed; Central America); Macleay, 1881: 366 (description; Australia); Vaillant, 1888: 5 (listed; Argentina). Acanthias americanus Storer, 1846: 506 (original description; United States of America); Gill, 1861: 60 (listed; North America). Spinax acantheus : Cuvier, 1863: 320 (cited). Acanthias lebruni Vaillant, 1888: 5, 13, 14, plate 1, fig. 2 (original description; Chile). Squalus lebruni : Berg, 1895: 6 (description; Argentina, Uruguay); Menni et al ., 1984: 62, 84 (listed; Argentina, Uruguay). Squalus blainvillei : Schreiner & Ribeiro, 1903: 79 (listed; Brazil); Miranda Ribeiro, 1907 (in part): 168 (description; Brazil). Squalus barbouri Howell-Rivero, 1936: 47, 48 (original description, not illustrated; Cuba). Squalus tasmaniensis Howell-Rivero, 1936 (original description, not illustrated; Tasmania); Last et al. , 2007: 109–113, figs. 1 B, 2 B (revision; Tasmania). Flakeus tasmaniensis : Whitley, 1940: 139, fig. 150 (listed; Australia). Koinga whitleyi : Whitley, 1940: 139, figs. 151, 152 (listed; Australia). Koinga kirki : Whitley, 1940: 140, fig. 153 (listed; Australia). Squalus kirki Phillipps, 1931 (original description, not illustrated; New Zealand). Squalus sp. of acanthias group: Figueiredo, 1981: 17 (listed; Brazil); Gomes et al ., 1997: 93 (description; Brazil); Marques, 1999 (cited; Brazil). Syntype . NRM 85, juvenile female, 177 mm TL, unknown locality. Donation by King Gustav IV Adolf of Sweden. Other possible syntypes in Uppsala (refuted by Wheeler, 1991): UUZM 159, juvenile male, 346 mm TL; UUZM 160, neonate female, 380 mm TL. Type locality: “Oceano Europaeo”. Possibly from off Sweden, Finland or Norway. Material examined (59 SWAO specimens) . AMNH 4099, neonate male, 230 mm TL, between the mouth of the rivers Coyle and Gallegos, Santa Cruz, Argentina; BMNH 1936.8. 26.17, adult male, 635 mm TL, near Strait of Magellan, Argentina, Southwestern Atlantic Ocean, 52.18 °S, 68 °W; BMNH 1999.5. 4.4, juvenile male, 550 mm TL, Falkland Islands, Southwest Atlantic Ocean; BMNH 1999.5. 4.13, juvenile female, 448 mm TL, Falkland Islands; BMNH 1999.5. 4.15, adult female, 535 mm TL, Falkland Islands; BMNH 1999.5. 4.16, juvenile male, 496 mm TL, Falkland Islands; HUMZ 30173, adult male, unknown TL, off Patagonia, Argentina, 47 °S, 6516 ’W (dissected); HUMZ 30178, adult male, 693 mm TL, off Patagonia, Argentina, 47 °S, 6516 ’W; HUMZ 30200, adult male, 655 mm TL, off Patagonia, Argentina, 47 °S, 6516 ’W; HUMZ 30285, adult male, 720 mm TL, off Patagonia, 47 °S, 6516 ’W; HUMZ 30291, adult male, 595 mm TL, off Patagonia, Argentina, 47 °S, 6516 ’W; HUMZ 30303, juvenile female, 487 mm TL, off Patagonia, 47 °S, 6516 ’W; HUMZ 30310, juvenile female, 520 mm TL, off Patagonia, Argentina, 47 °S, 6516 ’W; HUMZ 30324, adult male, 760 mm TL, off Patagonia, 47 °S, 6516 ’W; HUMZ 107285, juvenile female, 340 mm TL, off Argentina, 4659.5 ’S, 6516 ’W (dissected); MCT 7439, adult female, 587 mm TL, Tramandaí, Rio Grande do Sul, Brazil; MCZ 1435 -S, neonate male, 175 mm TL; neonate male, 205 mm TL, Suriname; MNRJ 509, juvenile male, 403 mm TL, Rasa Island, Rio de Janeiro, Brazil; MNRJ 513, juvenile female, 440 mm TL, Rasa Island, Rio de Janeiro, Brazil; NMW 83924, neonate male, 215 mm TL, unspecified locality, Brazil; ZMH 104416, adult male, 725 mm TL; adult female, 755 mm TL, near Peninsula del Valdes, Argentina, 5948 'W, 438 'S; ZMH 104461, two juvenile females, 510, 557 mm TL; one adult female, 742 mm TL, near Peninsula del Valdes, Argentina, 608 'W, 433 'S; ZMH 104519, two adult females, 670, 745 mm TL, near Cabo Blanco, Argentina, 6112 'W, 478 'S; ZMH 104951, adult male, 715 mm TL, near Santa Cruz, Argentina, 6340 'W, 490 'S; ZMH 104955, seven neonates males, 187–192 mm TL; five neonate females, 185–200 mm TL, near Santa Cruz, Argentina, 6546 'W, 4750 'S; ZMH 104968, six juvenile male, 226–233 mm TL; four juvenile female, 225–235 mm TL, near Cabo Blanco, Argentina, 6518 'W, 470 'S; ZMH 107911, four juvenile males, 213– 225 mm TL; six juvenile females, 215–223 mm TL, near Santa Cruz, Argentina, 640 'W, 460 'S; ZMH 108038, adult male, 670 mm TL, near Cabo Blanco, Argentina, 650 'W, 470 'S; ZMH 115469, juvenile male, 322 mm TL, near Santa Cruz, Argentina, 6324 'W, 4551 'S. Diagnosis . Squalus acanthias from the Southwestern Atlantic Ocean is distinguished from all local congeners by the following unique characters: rounded white spots dorsolaterally on body; anterior margin of nostrils unilobate; origin of first dorsal-fin spine behind the free rear tips of the pectoral fins; first dorsal-fin spine length much lower than fin height (first dorsal-fin spine length 1.5 %– 2.8 % TL vs . first dorsal-fin height 6.0%– 8.1 % TL); second dorsal-fin spine very elongated (1.9 %– 4.5 % TL), taller than second dorsal-fin apex; interdorsal distance 1.8 (1.5–2.2) times greater than dorsal-caudal distance; pectoral-pelvic distance 1.0 (0.6–1.3) times pelvic-caudal distance; dermal denticles unicuspid; coracoid bar with segmented processes anterolaterally. Description . External morphology . Measurements and counts are summarized in Tables 1 –2 (in the description of S. acanthias below, single values represent the mean followed by the range for non-type specimens from which data were taken). Body fusiform and slender, slightly more arched anteriorly as of posterior margin of spiracle to level of pectoral fin insertion; head height 0.8–1.1 times trunk height, and 0.8–1.5 times abdomen height. Head flattened, small (its length 18.4 %– 23.3 % TL) and broad, its width 1.2 (1.0– 1.5) times trunk width and 1.4 (1.1–2.2) times abdomen width. Snout somewhat elongate (5.8 %– 8.1 % TL), slightly obtuse in ventral view. Nasal apertures located laterally, small and slightly oblique; anterior margin of nostril unilobate or slightly bilobate in young specimens (Fig. 3); distance from snout tip to nostrils 1.0 (0.9–1.2) times distance from nostrils to upper labial furrow; prenarial length corresponding to half of preoral length; internarial distance 0.9 (0.6–1.4) times eye length. Eyes oval with anterior margin rounded and posterior margin angular, not notched; length 2.0 (1.4–3.5) times eye height; eyes closer to snout tip than to first branchial arch. Prespiracular length 1.7 (1.5 –2.0) times preorbital length and 0.6 (0.5–0.6) times pre-pectoral length. Spiracles crescent-shaped, located posterodorsally to eye, oblique in relation to longitudinal axis of body; diameter at least one-quarter eye length. Prebranchial length 1.5 (1.3–1.7) times prespiracular length. Gill slits concave, located in front of pectoral fins, tall with fifth gill slit 1.2 (0.7–1.7) greater in height than first gill slit. MeasurementsHolotypes Squalus S. barbouri S. tasmaniensis MCZ 1463 -S MCZ 146 -S N Range x SD TL (mm) 267.0 245.0 21 200.0–880.0 487.7 212.3 PCL 77.2 77.6 21 31.2–81.1 76.3 10.4 PD2 59.2 57.1 21 53.4–62.2 58.8 2.1 PD1 34.5 30.6 21 29.1–33.7 32.4 0.9 SVL 52.4 49.0 21 44.2–52.8 49.7 2.3 PP2 54.3 44.9 21 41.9–50.3 46.8 2.1 PP1 21.8 19.6 21 17.8–22.8 20.4 1.2 HDL 22.4 19.9 21 18.4–23.3 20.9 1.3 PG1 18.5 16.4 21 15.5–20.5 17.4 1.2 PSP 12.6 9.8 21 9.9–14.1 11.3 1.2 POB 7.0 5.4 21 5.8–8.1 6.9 0.6 PRN 5.1 3.3 21 3.8–5.1 4.5 0.4 POR 9.9 7.6 21 7.8–10.9 9.1 1.0 INLF 4.9 3.6 21 3.7–5.6 4.4 0.5 MOW 6.6 5.6 21 6.5–8.1 7.2 0.4 ULA 2.5 2.2 21 2.0–2.9 2.3 0.2 INW 2.8 3.2 21 2.8–4.8 3.4 0.4 INO 7.2 6.2 21 6.5–9.7 7.4 1.0 EYL 3.5 3.1 21 2.7–5.7 3.7 0.9 EYH 0.9 1.6 21 1.4–3.6 1.9 0.5 SPL 1.3 1.8 21 0.9–2.1 1.4 0.4 GS1 1.7 1.0 21 1.3–2.3 1.7 0.3 GS5 1.8 1.6 21 1.2–2.9 2.0 0.3 IDS 18.9 19.9 21 17.1–22.7 20.2 1.7 DCS 10.8 11.9 21 9.6–11.9 11.1 0.6 PPS 24.9 22.2 21 16.5–26.8 22.8 2.5 PCA 22.2 22.4 21 20.3–28.1 22.8 1.9 D1L 12.1 13.2 21 10.5–13.1 12.1 0.7 D1A 11.5 11.2 21 8.5–11.6 9.5 0.8 D1B 7.0 7.9 21 6.4–7.5 7.0 0.3 D1H 7.8 6.9 21 6.0–8.1 6.7 0.4 D1I 5.7 5.8 21 4.4–6.0 5.2 0.4 ......continued on the next page TABLE 1. (Continued) Mouth arched and evidently broad, its width 1.6 (1.4–1.9) times prenarial length and 2.1 (1.6–2.5) times internarial space; upper labial furrow slender and large, its length corresponding to 2.0%– 2.9 % TL; lower labial furrow inconspicuous. Teeth unicuspid, similar in both jaws, flattened labial-lingually and laterally overlapped; teeth broad, although short at crown; upper teeth smaller than lower teeth; cusp thick and elongate, oblique and directed laterally (cusp strongly vertical in most adult males); convex mesial cutting edge; both distal and mesial heels rounded; apron well elongated in both jaws; one intermediate tooth present at least in upper jaw, usually smaller than the following teeth, with cusp completely vertical, short apron, and both distal and mesial heels markedly rounded; two series of functional teeth in upper and lower jaws; teeth rows varying from 14 – 1–14 in upper jaw and 11 – 1–12 in lower jaw (Fig. 4).Origin of first dorsal fin posterior to free rear tips of pectoral fin; in young specimens, origin over free rear pectoral tips (pre-first dorsal length 29.1 %– 33.7 % TL in neonates and juveniles); horizontal distance between origins of pectoral fin and first dorsal fin 1.8 (1.2–2.3) times preorbital length. First dorsal fin vertical and markedly wide at its fin web, relatively large (10.5 %– 13.1 % TL) and low, its length 1.8 (1.5–2.1) times its height, its height and base length 1.0 (0.9–1.2) times preorbital length; anterior margin convex, posterior margin moderately concave near free rear tip; apex rounded, and free rear tips pointed; inner margin length 0.8 (0.6–0.9) times fin height. Origin of first dorsal-fin spine slightly posterior to free rear tips of pectoral fins. First dorsal-fin spine conspicuously slender and low, its length not greater than half dorsal-fin height, never reaching fin apex. Interdorsal distance 1.0 (0.8–1.3) times prepectoral length and 1.8 (1.5–2.2) times dorsal-caudal distance. Pre-second dorsal length 4.3 (3.7–5.2) times the anterior margin length of pectoral fin and 2.9 (2.6–3.2) times dorsal caudal lobe length. Second dorsal fin rather oblique and broad at its fin web, relatively large, its length 1.0 (0.9–1.2) times first dorsal-fin length, and 2.5 (1.9 –3.0) times second dorsal-fin height; anterior margin convex and posterior margin falcate; apex rounded, and free rear tip pointed; inner margin elongate, its length 1.0 (0.8–1.1) times fin height. Second dorsal-fin spine slightly inclined, elongated (1.9 %– 4.5 % TL) and reaching the fin apex (in some adult specimens, second spine exceeds the fin apex); slender and low, its length 0.7 (0.4–0.9) times second dorsal-fin height and 1.8 (1.3–2.5) times first dorsal-fin spine length; second dorsal-fin spine broader than first dorsal-fin spine, its base length 1.3 (1.0– 1.5) times first dorsal-fin spine base length. Pre-pectoral length 0.6 (0.6–0.7) times pre-first dorsal length, 0.4 (0.4–0.5) times pre-vent length. Pectoral fins with both anterior and inner margins convex, and posterior margin straight; anterior margin length 1.6 (1.4–1.6) times posterior margin length, but its tip reaches same level of its apex; apex and free rear tips evidently rounded, but not lobe-like; pectoral fin base length varying from 3.2 %– 5.2 % TL. Pelvic fins narrow and elongate, their length 8.6 %– 12.4 % TL anterior margin; slightly convex and posterior margin straight; apex and free rear tips rounded, the latter lobe-like; origin of pelvic fins 1.8 (1.5 –2.0) times distance between origins of the two dorsal fins, nearest to second dorsal fin (in young specimens, nearest to first dorsal fin); pectoral-pelvic distance 1.0 (0.6–1.3) times pelvic-caudal distance, usually equal in adults. Clasper cylindrical, compressed dorsoventrally throughout its extension, greatly extended beyond free rear tips of pelvic fin, its outer length 1.1 %– 5.8 % TL; siphon large, located medioventrally from the anteriormost end of puboischiadic bar level of intermediate cartilage; clasper groove longitudinal and dorsomedially, sinuous and deep; apopyle broad, placed more anteriorly in clasper groove; hypopyle narrow, located posteriorly to rhipidion; rhipidion elongate, blade-like, located medially at distal end of clasper (Fig. 5). Caudal peduncle with inconspicuous lateral keels, originating behind insertion of second dorsal fin; upper and lower precaudal pits marked. Caudal fin conspicuously rectangular on dorsal lobe with dorsal-caudal margin straight and upper postventral margin strongly convex; dorsal-caudal margin length 1.0 (0.9–1.1) times head length and 1.8 (1.7 –2.0) times preventral margin length; caudal fork markedly concave and broad, its width corresponding to 6.0%– 7.4 % TL; lower postventral margin also convex; preventral caudal margin convex and large, its length 2.4 (1.7–3.5) times pelvic fin inner margin length. Dermal denticles (Fig. 7). Denticles unicuspid, their length and width equivalent, relatively sparsely positioned, not imbricated; median ridge pronounced, elongate and narrow, projecting anteriorly beyond crown base; median cusp pointed posteriorly. In neonates, denticles smaller, markedly sparse and underdeveloped throughout body. Coloration (Figs. 2, 6). Body dark gray dorsal and laterally, and light gray more posteriorly from the lower lateral half of the body just in front of the pectoral fin origin to the caudal fin; white ventrally; large and few paired white spots dorsolaterally, usually ant : Published as part of De, Sarah T., De, Marcelo R. & Gomes, Ulisses L., 2016, Taxonomy and morphology of species of the genus Squalus Linnaeus, 1758 from the Southwestern Atlantic Ocean (Chondrichthyes: Squaliformes: Squalidae), pp. 1-89 in Zootaxa 4133 (1) on pages 8-29, DOI: 10.11646/zootaxa.4133.1.1, http://zenodo.org/record/400024 : {"references": ["Linnaeus, C. (1758) Systema Naturae. Systema naturae per regna tria naturae, secundum classes, ordines, genera, species, cum characteribus, differentiis, synonymis, locis. Tomus I. Editio decimal, reformata. Tomus I. Impensis Direct. Laurentii Salvii, Holmiae, 824 pp.", "Rafinesque, C. S. (1810) Indice d'ittiologia siciliana; ossia, catalogo metodico dei nomi latini, italiani, e siciliani dei pesci, che si rinvengono in Sicilia disposti secondo un metodo naturale e seguito da un appendice che contiene la descrizione de alcuni nuovi pesci sicilian. Presso Giovanni del Nobolo, con approvazzione, Messina, 70 pp.", "Gill, T. N. (1862) Analytical synopsis of the order of Squali; and revision of the nomenclature of the genera. Annals of the Lyceum of Natural History of New York, 7 (art. 32), 367 - 413. http: // dx. doi. org / 10.1111 / j. 1749 - 6632.1862. tb 00166. x", "Berg, C. (1895) Enumeracion sistematica y sinonimica de los peces de las costas Argentina y Uruguaya. Anales del Museo Nacional de Historia Natural de Buenos Aires, 4, 1 - 120.", "Jordan, D. S. & Evermann, B. W. (1896) The fishes of North and Middle America: a descriptive catalogue of the species of fishlike vertebrates found in the waters of North America, north of the Isthmus of Panama. Part I. Bulletin of the United States National Museum, 47, 1 - 1240.", "Schreiner, C. & Miranda Ribeiro, A. (1903) A colecao de peixes do Museu Nacional do Rio de Janeiro. Arquivos do Museu Nacional, 12, 1 - 108.", "Regan, C. T. (1908) A synopsis of the sharks of the family Squalidae. Annals and Magazine of Natural History, Series 8, 2 (7), 39 - 57.", "Garman, S. (1913) The Plagiostomia (sharks, skates and rays). Memoirs of the Museum of Comparative Zoology, Harvard College, 36, 1 - 515.", "Fowler, H. W. (1936) The marine fishes of West Africa based on the collection of the American Museum Congo expedition, 1909 - 1915. Part II. Bulletin of the American Museum of Natural History, 70 (2), 607 - 1493.", "Bigelow, H. B. & Schroeder, W. C. (1948) Sharks. In: Tee-Van, J., Breder, C. M., Hildebrand, S. F., Parr, A. E. & Schroeder, W. C. (Eds.), Fishes of the Western North Atlantic. Part 1. Memoir Sears Foundation for Marine Research, Yale University, New Haven, pp. 1 - 576.", "Bigelow, H. B. & Schroeder, W. C. (1957) A study of the sharks of the suborder Squaloidea. Bulletin of the Museum of Comparative Zoology, Harvard College, 117 (1), 1 - 150.", "Garrick, J. A. F. (1960) Studies on New Zealand Elasmobranchii. Part XII. The species of Squalus from New Zealand and Australia; and a general account and key to the New Zealand Squaloidea. Transactions of the Royal Society of the New Zealand, 88 (3), 519 - 557.", "Bass, A. J., D'Aubrey, J. D. & Kistnasamy, N. (1976) Sharks of the east coast of southern Africa. VI The families Oxynotidae, Squalidae, Dalatiidae and Echinorhinidae. Investigational Report, Oceanographic Research Institute, 45, 1 - 103.", "Cadenat, J. & Blache, J. (1981) Requins de Mediterranee et d'Atlantique (plus particulierment de La Cote Ocidentale d'Afrique). Fauna Tropicale. ORSTOM, Paris, 330 pp.", "Lucena, C. A. S. & Lucena, Z. M. S. (1981) Catalogo dos peixes marinhos do Museu de Ciencias da Pontificia Universidade Catolica do Rio Grande do Sul. Elasmobranchii. Teleostomi (1 parte). Comunicacoes do Museu de Ciencias da PUCRGS, 21, 1 - 66.", "Compagno, L. J. V. (1984) FAO Species Catalogue. Vo. 4. Sharks of the world. An annotated and illustrated catalogue of shark species known to date. Part 1. Hexanchiformes to Lamniformes. FAO Fisheries Synopsis, Rome, 4 (125), 1 - 249.", "Kondyurin, V. V. & Myagkov, N. A. (1984) Sharks of the genus Squalus of the western Atlantic ocean. Journal of Ichthyology, 24 (3), 118 - 121.", "Menni, R. C., Ringuelet, R. A. & Arambaru, R. H. (1984) Peces marinos de la Argentina y Uruguay. Resena historica: clave de familias, generos y especies: catalogo critico. Editorial Hemisferio Sur AS, Buenos Aires, 359 pp.", "Myagkov, N. A. & Kondyurin, V. V. (1986) Dogfishes, Squalus (Squalidae) of the Atlantic Ocean and comparative notes on the species of this genus from other regions. Journal of Ichthyology, 26 (6), 1 - 18.", "Lessa, R., Santana, F. M., Rincon, G., Gadig, O. B. F. & El-Deir, A. C. A. (1999) Biodiversidade de elasmobranquios do Brasil. MMA / PROBIO, Necton, Elasmobranquios, Recife, 154 pp.", "Gadig, O. B. F. (2001) Tubaroes da Costa Brasileira. Unpublished PhD Thesis. Instituto de Biociencias da Universidade Estadual Paulista \" Julio de Mesquita Filho, Rio Claro, 343 pp.", "Soto, J. M. R. (2001) Annotated systematic checklist and bibliography of the coastal and oceanic fauna of Brazil. I. Sharks. Mare Magnum, 1 (1), 51 - 120.", "Compagno, L. J. V. (2002) Sharks. In: Carpenter, K. E. (Ed.), The living marine resources of the Western Central Atlantic. Vol. 1. Introduction, molluscs, crustaceans, hagfishes, sharks, batoid fishes and chimaeras. FAO Species identification guide for fishery purposes and American Society of Ichthyologists Special Publication 5. FAO, Rome, pp. 357 - 505.", "Meneses, P. & Paesch, L. (2003) Guia de campo para la identificacion de peces cartilaginosos em el Rio de da Plata y su frente oceanico. Direccion Nacional de Recursos Acuaticos, Montevideo, 55 pp.", "Soto, J. M. R. & Mincarone, M. M. (2004) Collections of the Museu Oceano grafico do Vale do Itaja. I. Catalog of cartilaginous fishes (Myxini, Cephalaspidomorphi, Elasmobranchii, Holocephalii). Mare Magnum, 2 (1 - 2), 1 - 125.", "Lamilla, J. & Bustamante, C. (2005) Guia para el reconocimiento de tiburones, rayas y quimeras de Chile. Oceana, 17, 1 - 80.", "Gomes, U. L., Signori, C. N., Gadig, O. B. F. & Santos, H. R. S. (2010) Guia para Identificacao de Tubaroes e Raias do Rio de Janeiro. Technical Books, Rio de Janeiro, 234 pp.", "Viana, S. T. de F. (2011) Revisao taxonomica e morfologica do genero Squalus Linnaeus, 1758 do oceano Atlantico Sul Ocidental (Chondrichthyes: Squaliformes: Squalidae). Unpublished MSc Thesis. Departamento de Zoologia, Instituto de Biociencias, Universidade de Sao Paulo, Sao Paulo, 348 pp.", "Rosa, R. S. & Gadig, O. B. F. (2014) Conhecimento da diversidade dos Chondrichthyes marinhos no Brasil: a contribuicao de Jose Lima de Figueiredo. Arquivos de Zoologia, 45, 89 - 104. http: // dx. doi. org / 10.11606 / issn. 2176 - 7793. v 45 iespp 89 - 104", "Molina, G. I. (1782) Saggio sulla storia naturale del Chile, del Signor Abate Giovanni Ignazio Molina. Saggio Chile, Bologna, 306 pp. http: // dx. doi. org / 10.5962 / bhl. title. 62689", "Risso, A. (1826) Histoire Naturelle des principales productions de L' Europe Meridionale et particulierement de celles des environs de Nice et des Alpes Maritimes. Tome III. Chez F. - G. Levrault, libraire, Paris, 480 pp.", "Muller, J. & Henle, J. (1841) Systematische Beschreibung der Plagiostomen. Veit, Berlin, 300 pp. http: // dx. doi. org / 10.5962 / bhl. title. 6906", "Dumeril, A. H. A. (1865) Histoire naturelle des poissons ou ichthyologie generale. Tome Premier. I. Elasmobranches. Plagiostomes et Holocephales ou Chimeres. Tableau elementaire de l'histoire naturelle des animaux, 1, 1 - 720.", "Macleay, W. (1881) A descriptive catalogue of Australian fishes. Part IV. Proceedings of the Linnean Society of New South Wales, 6 (2), 202 - 387.", "Gill, T. N. (1861) Catalogue of fishes of the Eastern coast of North America, from Greenland to Georgia. Proceedings of the Academy of Natural Sciences of Philadelphia, 13, 1 - 63.", "Miranda Ribeiro, A. (1907) Fauna Brasiliense. Peixes II (Desmobranchios). Arquivos do Museu Nacional, 14, 131 - 217.", "Figueiredo, J. L. de (1981) Estudo das distribuicoes endemicas de peixes da Provincia Zoogeografica Marinha Argentina. Unpublished PhD Thesis. Departamento de Zoologia, Instituto de Biociencias, Universidade de Sao Paulo, Sao Paulo, 121 pp.", "Gomes, U. L., Lima, M. C., Parago, C. & Quitans, A. P. (1997) Catalogo das colecoes ictiologicas do Departamento de Biologia Animal e Vegetal. Instituto de Biologia da Universidade Estadual do Rio de Janeiro, Rio de Janeiro, Grafica UERJ, 185 pp.", "Marques, A. R. (1999) O genero Squalus no Brasil: caracterizacao do grupo megalops e determinacao do status taxonomico das formas brasileiras. Unpublished Msc. Thesis. Universidade do Estado do Rio de Janeiro, Rio de Janeiro, 117 pp.", "Wheeler, A. C. (1991) The Linnaean fish collection in the Zoological Museum of the University of Uppsala. Zoological Journal of the Linnean Society, 103 (2), 145 - 195. http: // dx. doi. org / 10.1111 / j. 1096 - 3642.1991. tb 00901. x", "Ebert, D. A., Fowler, S. & Compagno, L. J. V. (2013) Sharks of the World: A Fully Illustrated Guide. Wild Nature Press, London, 528 pp.", "Fernholm, B. & Wheeler, A. (1983) Linnaean fish specimens in the Swedish Museum of Natural History, Stockholm. Zoological Journal of the Linnean Society, 78, 199 - 286. http: // dx. doi. org / 10.1111 / j. 1096 - 3642.1983. tb 00867. x", "Gallucci, V. F., McFarlane, G. A. & Bargmann, G. G. (2009) Biology and management of dogfish sharks. American Fisheries Society, Bethesda, Maryland, 435 pp.", "Verissimo, A., McDowell, J. R. & Graves, J. E. (2010) Global populational structure of the spiny dogfish Squalus acanthias, a temperate shark with an antitropical distribution. Molecular Ecology, 19, 1651 - 1662. http: // dx. doi. org / 10.1111 / j. 1365 - 294 X. 2010.04598. x", "Springer, V. G. & Garrick, J. A. F. (1964) A survey of vertebral numbers in sharks. Proceedings of the United States National Museum, 116 (3496), 73 - 96. http: // dx. doi. org / 10.5479 / si. 00963801.116 - 3496.73", "Ward, R. D., Holmes, B. H., Zemlak, T. S. & Smith, P. J. (2007) DNA barcoding discriminates spurdogs of the genus Squalus. In: Last, P. R., White, W. T. & Pogonoski, J. J. (Eds.), Descriptions of new dogfishes of the genus Squalus (Squaloidea: Squalidae). CSIRO Marine and Atmospheric Research Paper, 14, pp. 117 - 130.", "Ebert, D. A., White, W. T., Goldmann, K. J., Compagno, L. J. V., Daly-Engel, T. S. & Ward, R. D. (2010) Resurrection and redescriptions of Squalus suckleyi (Girard, 1854) from the North Pacific, with comments on the Squalus acanthias subgroup (Squaliformes: Squalidae). Zootaxa, 2612, 22 - 40.", "Lindberg, G. U. & Legeza, M. I. (1956) On two forms of spiny dogfish Squalus acanthias L. Zoologicheskii Zhurnal, 35 (11), 1685 - 1688. [in Russian]", "Lindberg, G. U. & Legeza, M. I. (1959) Fishes of the Sea of Japan and adjacent parts of the Okhotsk and Yellow Sea. Part 1. Amphioxi, Petromyzones, Myxini, Elasmobranchii, Holocephalii. Opredeliteli Faune SSSR, 68, 1 - 207.", "Howell-Rivero, L. (1936 a) A new shark from Tasmania. Occasional Papers of the Boston Society of Natural History, 8, 267 - 268."]}